Analysing the Future of International Criminal Justice in Africa: A Focus on the ICC - Ngolo, Emily (Strathmore Law Review, 2016)
The International Criminal Court has generally a bad reputation in the African continent as a whole with hostile assertions by the African Union, that the court is nothing but a political tool for the powerful. The Court, plagued with numerous difficulties, has come under pressure to perform, with some doubting its viability. Created by the Rome Statute, and the parties therein governed by general treaty law, enforcement mechanisms of the court have been unsatisfactory at best and this has led to questions being asked as to its survival. There exists a pool of divergent views, in regard to the African Union and the International Criminal Court, in many of the crucial areas of international criminal justice. This paper seeks to find out just how true is the claim that the ICC is ‘dead’ is, and the implications of this in the future of the continent as regards international criminal justice. How important is it for us to preserve international criminal justice? Just how much of a role do states play in this revered area of law? Is its legal viability coming to an unfortunate premature end? What does this mean, then, for the victims of mass atrocities? This paper seeks to show an interplay of the role of states and politics in international criminal justice, and determine then, whether there exists any bright future for this area of law in Africa.